1999
DOI: 10.1523/jneurosci.19-05-01736.1999
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Mechanisms Subserve Attention in Macaque Areas V2 and V4

Abstract: It is well established that attention modulates visual processing in extrastriate cortex. However, the underlying neural mechanisms are unknown. A consistent observation is that attention has its greatest impact on neuronal responses when multiple stimuli appear together within a cell's receptive field. One way to explain this is to assume that multiple stimuli activate competing populations of neurons and that attention biases this competition in favor of the attended stimulus. In the absence of competing sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

137
1,084
11
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,130 publications
(1,239 citation statements)
references
References 43 publications
137
1,084
11
7
Order By: Relevance
“…Similarly, it has been reported that the product of within-modal visual interactions in cortical visual neurons is in most cases subadditive (Movshon et al, 1978;Henry et al, 1978, Britten andHeuer, 1999;Carandini et al, 1997;Reynolds et al, 1999;Gawne and Martin, 2002;Lampl et al, 2004;Li and Basso, 2005). These observations prompt the search for more appropriate models to describe the products of unisensory integration.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, it has been reported that the product of within-modal visual interactions in cortical visual neurons is in most cases subadditive (Movshon et al, 1978;Henry et al, 1978, Britten andHeuer, 1999;Carandini et al, 1997;Reynolds et al, 1999;Gawne and Martin, 2002;Lampl et al, 2004;Li and Basso, 2005). These observations prompt the search for more appropriate models to describe the products of unisensory integration.…”
Section: Discussionmentioning
confidence: 89%
“…The additive model predicts that the response to two stimuli will be equivalent to the sum of the responses evoked by the stimuli individually (Stanford et al, 2005;Alvarado et al, 2007aAlvarado et al, ,2007b). The averaging model predicts that the response to two stimuli will be equivalent to the mean of the responses evoked by the stimuli individually (Heeger, 1992;Rolls and Tovee, 1995;Carandini et al, 1997;Recanzone et al, 1997;Britten and Heuer, 1999;Reynolds et al, 1999;Treue et al, 2000;Heuer and Britten, 2002;Zoccolan et al, 2005). The maximum operator model predicts that the response to two stimuli will be equivalent to the strongest response evoked by either stimulus individually (Riesenhuber and Poggio 1999;Gawne and Matin 2003;Lampl et al, 2004).…”
Section: Evaluating Models For Unisensory Integrationmentioning
confidence: 99%
“…Activating an expectation of 'yellow balls' enables more rapid detection of a yellow ball, and with a more energetic neural response, than if you were not looking for it. Neural correlates of such excitatory priming and gain control have been reported by several laboratories [46][47][48][49][50][51][52] . Sensory and cognitive topdown expectations hereby lead to excitatory matching with confirmatory bottom-up data.…”
Section: Complementary Expectation Learning and Matching During 'Whatmentioning
confidence: 81%
“…A good example where this is relevant is in selective attention (Reynolds and Desimone 2003), where two stimuli are presented within the receptive field of a single neuron. Experimental studies in visual cortex (Treue and Maunsell 1996;Luck et al 1997;Reynolds et al 1999;Reynolds and Desimone 2003) have shown that the output of a neuron may reflect either input, depending on whether attention is directed to one or the other stimulus. This biasing of competition in favour of the attended stimulus is correlated with the appearance of enhanced gamma band (30-80 Hz) synchronization (Fries et al 2001(Fries et al , 2007Fries 2009;Gruber et al 1999;Taylor et al 2005;Womelsdorf et al 2005).…”
Section: Introductionmentioning
confidence: 99%